Interventions for chronic kidney disease in people with sickle cell disease (Protocol) - Roy, N; Fortin, P; Bull, K; Doree, C; Trivella, M; Hopewell, S; Estcourt, L (John Wiley & Sons, Ltd, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effectiveness of any intervention in preventing or reducing kidney complications or CKD in people with SCD (including red blood cell transfusions, hydroxyurea and ACEI (either alone or in combination with each other)).